An overview of electronic corner reflectors and their use in ground deformation monitoring applications - Fotiou, Kyriaki; Danezis, Chris (My University, 2020)
Over the years, passive and active reflectors are becoming indispensable parts in ground deformation monitoring using Interferometric SAR geodetic techniques. The evolution and the need for more practical and compact in size reflectors motivated the implementation of Electronic Corner Reflectors, namely ECR Transponders. ECR Transponders are compact active permanent scatterers, which are used in the estimation of physical or man-induced deformation processes. Their main advantage lies their compact size and the fact that a sole unit accounts for both ascending and descending tracks, instead of having two opposite-facing ordinary Corner Reflectors configuration. To date, ECR transponders mainly operate in C-band and, thus, are compatible with Sentinel-1 and Radarsat. Although experiments are in initial stage, the results seem quite promising with respect to the classic passive corner reflectors in many sectors. In this paper, an analysis of the ECR-C band transponders is carried out, along with a worldwide overview and a comparison of their results in various application sectors using different satellite radar missions and techniques.
Keywords: Corner Reflectors; Deformation Monitoring; InSAR; Natural Hazards; SAR Transponders